Analysis of tensegrity structures subject to dynamic loading using a Newmark approach - Faroughi, Shirko; Lee, Jaehong (Journal of Building Engineering, 2015)
Tensegrities are lightweight structures whose integrity is based on a balance between tension and compression. In general, these systems have low structural damping, and this leads to a challenge when they are subjected to dynamic loading. This paper presents an analysis for linearized dynamic tensegrity structures under dynamic loading near the equilibrium configuration using a Newmark method. Numerical examples are presented to demonstrate the effectiveness of the proposed scheme. The Newmark method is more efficient than other classical approaches to solve dynamical tensegrity structure models. Here, the effects of damping and slackening condition on dynamic analysis of tensegrity structures are also investigated. •Analysis of a linearized dynamic tensegrity structures model under dynamic loading.•Newmark method is proposed as a general method that is able to solve dynamic equilibrium equations.•The effects of damping and slacking condition on dynamic analysis of tensegrity structure are investigated.